Performance analysis of BER and channel capacity of MIMO-OSTBC using adaptive modulation techniques - Arvind, Sudha; S. Arvind, Dr (International Journal of Engineering and Technology, 2018)
As per today’s scenario the information transmission is needed with highly effective communication in terms of greater speeds of data transmission, more accuracy and high reliability. Multiple-Input Multiple-Output (MIMO) Communication System is more suitable for ro-bust and secure communication with high speed data transmission. Here in this paper how MIMO is more suitable than SISO, SI-MO (Single-Input Multiple-output) and MISO(Multiple-input single-output) is shown in terms of better Channel Capacity and less BER (Bit Error Rate). OSTBC Encoder and Decoders are used for secure communication is estimated and analyzed for BPSK, QPSK with SISO and MIMO(3 outputs and two inputs-3x2 fading channel) Communication System for ½ and ¾ coding rates with AWGN Channel as transmis-sion. Adaptive Quadrature Modulation technique (QAM) is used with M-ary values of 16,24 and 256 for ½ and ¾ coding rates for both SISO and MIMO (3x2 Fading Channel) Communication System. As per the Simulation results BER and Channel capacity performances for MIMO are better compared with SISO with Adaptive Modulation Techniques.